Sub-GeV Gamma Rays from Nearby Seyfert Galaxies and Implications for Coronal Neutrino Emission - Kohta Murase; Christopher M. Karwin; Shigeo S. Kimura; Marco Ajello; Sara Buson (The Astrophysical Journal Letters, 2024)
Recent observations of high-energy neutrinos by IceCube and gamma rays by the Fermi Large Area Telescope (LAT) and the MAGIC telescope have suggested that neutrinos are produced in gamma-ray opaque environments in the vicinity of supermassive black holes. In this work, we present 20 MeV–1 TeV spectra of three Seyfert galaxies whose nuclei are predicted to be active in neutrinos, NGC 4151, NGC 4945, and the Circinus galaxy, using 14.4 yr of Fermi LAT data. In particular, we find evidence of sub-GeV excess emission that can be attributed to gamma rays from NGC 4945, as was also seen in NGC 1068. These spectral features are consistent with predictions of the magnetically powered corona model, and we argue that NGC 4945 is among the brightest neutrino active galaxies detectable for KM3Net and Baikal-GVD. On the other hand, in contrast to other reported results, we do not detect gamma rays from NGC 4151, which constrains neutrino emission from the accretion shock model. Future neutrino detectors such as IceCube-Gen2 and MeV gamma - ray telescopes such as AMEGO-X will be crucial for discriminating among the theoretical models.